The Influence of Problem-Based Learning Model to Indonesian Language Primary Classrooms: A Meta-Analysis - Suparjan, Suparjan; Haryanto, Haryanto; Murjainah, Murjainah; Ismiyani, Nining (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Indonesian language is a subject that must be taught at the elementary school level, and many studies have been conducted to evaluate how the application of certain learning models and strategies influences the teaching and learning process to improve students' Indonesian language skills. This meta-analysis study is intended to examine the effects of Problem Based Learning on Indonesian language learning achievement in elementary schools in Indonesia.The study utilized meta-analysis methodology by analyzing research literature data, specifically the learning outcomes resulting from the implementation of PBL in Indonesian language subject at the elementary school level. The data for this study were collected through documentary study technique, which involved gathering electronic articles related to the utilization of PBL in Indonesian language subjects at the elementary school level from indexed journals such as Google Scholar and Sinta. Based on the results of the meta-analysis, it can be concluded that the PBL model is capable of enhancing students' cognitive learning outcomes. Furthermore, based on the t-test, indicating that the PBL instructional model has a significant impact on Indonesian language learning outcomes in elementary school students, as evidenced